Volume and territorial distribution of the Czech Republic's official development assistance flows to least developed countries - Eva Kovářová (Review of Economic Perspectives, 2021)
Official Development Assistance (ODA) is considered one of the most important external resources of finance that can contribute to sustainable development in the Least Developed Countries (LDCs). The Czech Republic, as an official donor country, should spend on ODA, with respect to the EU and national targets, at least 0.33% of its GNI by the year 2030. Eradication of poverty in the context of sustainable development belongs to the long-term priorities of the Czech foreign development cooperation, and thus the Czech Republic considers some LDCs, which population is more likely to live in extreme poverty, the priority partner countries. Paper evaluated fundamental trends of the Czech Republic's ODA flows to LDCs; compared them with the trends identified for the collective flows of all DAC members and for the flows of its four selected members (Hungary, Poland, Slovakia, Slovenia). Identified trends of Czech ODA flows showed clearly that Czech Republic did not meet official commitments regarding the volume of ODA and that level of fragmentation of the ODA flows to LCDs was quite high when these trends were examined during the period 2000-2018. However, the Czech Republic's development cooperation policy did not differ markedly from the policies of the other four ODA donors. Any significant differences were identified when the fundamental trends of Czech ODA flows were compared with those ones identified for Hungary, Poland, Slovakia and Slovenia.
Keywords: F35; F43; F63; 330; Czech Republic; Least Developed Countries; Official Development Assistance; Sustainable Development